Parnassus and Canonization in “Espejo, dime” by Luis García Montero: an Intertextual Dialogue between Golden and Contemporary Voices (Castilla. Estudios de Literatura, 2011)
The present article offers a monographic analysis of the composition “Espejo, dime”, by Luis García Montero (Granada, 1958), belonging to the poems Rimado de ciudad (1983). In a first level of study, it is analyzed, on one hand, the generic characterization of the poem and, on the other, the presence of Parnassus’s technique like a mechanism of canonization, also used by outstanding authors of the Spanish Literature of the Golden Century like Cervantes, Juan de la Cueva and Lope de Vega. In parallel, contemporary sources handled by the author are identified, among those highlights Antonio Machado, Manuel Altolaguirre, Federico García Lorca and Jaime Gil de Biedma.